Analyzing Important Elements for Improving the Safety of Motorways - Kim, Yejin; Lee, Yoseph; Lee, Youngtaek; Ko, Woori; Yun, Ilsoo (Applied Sciences (Switzerland), 2024)
This study aims to identify the factors that influence the occurrence of traffic accidents to improve motorway traffic safety. Various data, including the frequency of traffic accidents, traffic volume, geometric structure, and congestion level, were collected from individual sections of motorways in South Korea. Using the collected data, a traffic accident frequency prediction model was developed by applying an explainable artificial intelligence (AI)-based approach. The developed deep neural network model was combined with Shapley Additive Explanations to identify the variables that significantly affect the frequency of traffic accidents. The analysis identified five significant factors: segment length, total traffic volume, the proportion of truck traffic, the number of dangerous driving behaviors, and the duration of congestion. The results demonstrate the potential of using explainable AI in predicting traffic accident frequency. By identifying the factors that influence traffic accidents using this model, we can pinpoint areas for improvement, which may ultimately help reduce highway traffic accidents.
Keywords: Accident frequency; Congestion level; Explainable artificial intelligence (XAI); Geometric structure; Motorway; Neural-networks; Shapley; Shapley additive explanation; Traffic safety; Traffic volumes; deep neural network; explainable AI (XAI); motorway; safety; Shapley Additive Explanation (SHAP)